All-fiber-coupled, master oscillator fiber power amplifier based laser assembly for the LISA gravitational wave detector - Weise, Dennis; Limpert, Jens; Schreiber, Thomas; Braxmaier, Claus; Wührer, Christian; Gath, Peter; Schulte, Hans Reiner; Tünnermann, Andreas; Johann, Ulrich (Proceedings of SPIE - The International Society for Optical Engineering, 2017)
We review possible alternatives for the realization of the LISA laser assembly against the requirements and present a concept for a tailored master oscillator fiber power amplifier solution. An all-solid-state, all- fiber coupled approach with a Nd:YAG NPRO seed appears particularly attractive due to the possibility to combine excellent spectral properties and high output powers with superior environmental robustness.
CRIS-Team Scopus Importer:2023-04-20